Relationship between components of subjective well-being and sociodemographic variables in older schoolchildren - Šarakauskienė, Živilė; Bagdonas, Albinas (Psichologija, 2010)
This research is focused on the importance of the adolescents’ subjective well-being (SWB) evaluation and on filling the in Lithuania lack of data on this topic. The aim of the study was to assess various SWB components and their relationship with the sociodemographic variables in the older schoolchildren’s sample (N = 655). The following SWB components were evaluated: satisfaction with life (Cronbach’s α = 0.79) and important specific domains (family (α = 0.83), school (α = 0.87), friends (α = 0.83), self (α = 0.77), living environment (α = 0.82)), positive and negative affects (respectively α = 0.77 and α = 0.87). Also, the following sociodemographic variables were measured: gender (58% girls), class (age) (8th (mean 14 years), 10th (16 years), 12th (18 years)), living place (41.8% from five biggest cities, 36.8% from regional towns, 21.4% from villages), learning success, family composition, parents’ education and employment, whether money is received for minor expences. Older schoolchildren evaluated by highest points satisfaction with friends (4.51–4.93) and self (4.30–4.70) and by the lowest – satisfaction with school (3.20–3.99) and living environment (3.12–4.21). Girls scored higher points in satisfaction with school (3.73 ± 0.95), negative affect (2.16 ± 0.68) scales in comparison with boys (3.50 ± 0.96 and 2.05 ± 0.64, respectively). Statistically significant differences of SWB components were most frequent among groups of school children of different age. No statistically significant relationships were found among group means according to the mother’s occupation. A relationship was found among SWB components and age, living place, learning success, family composition, parents’ education, whether money is received for minor expenses. Values of SWB components were higher for schoolchildren who learn in the eighth grade, live in a village, succeed better in learning, live with two parents, whose parents have a higher degree of education, and who receive money for minor expenses.